Appropriate Risk Factors for Preterm Labor Screening - Urairoekkun, Chonlatit (Journal of Health Science of Thailand, 2017)
The objectives of this study were to assess the magnitude and the risk of preterm labour in order to identify the suitable risk factors for pretern labour screening. It was conducted as a retrospective case-control study among 52,924 pregnant women delivered in the public health region 5 during 2009-2015. Data were collected from medical records, of which 4,272 caes were preterm deliveries (the study group); and the same variables among 48,652 term births were used as control. It was found that the prevalence of preterm birth in public health region 5 was equal 8.1%, the percentage of low birth weight was 9.1% and birth asphyxia was equal to 21.3 per 1000 lived birth. Odds ratio of low birth weight and birth asphyxia in the preterm compared with the term births was 16.3 and 3.9 respectively, and the difference was statistically significanct. The risk factors for preterm birth were history of second spontaneous abortion [OR=1.4 (1.2-1.8)], twin pregnancy [OR=9.5 (7.4-12.1)], age >35 year [OR=1.3 (1.1-1.6)], age <15 year [OR=2.1 (1.3-3.5)], anemia (hematocrit <33%) [OR=1.9 (1.2-2.9)], BMI <18.5 kg/m2 [OR=1.2 (1.1-1.3)], pregnancy induced hypertension [OR=2.5 (1.8-3.5)], and gestational DM [OR=2.4 (1.6-3.6)]. In clinical practice, history of previous preterm delivery or cervical length measured by vaginal ultrasound less than 2.5-3.0 cm. was used as the indication for using progesterone to prevent preterm labour. If the service providers could not screen all cases of pregnant women by vaginal ultrasound due to limitation of resources, applying screeing procedure using one or more risk factors to select high risk cases for cervical length measurement by vaginal ultrasound could reduce the workload by 53.0%.